PEMANFAATAN MEDIA RADIO BELITUNG TIMUR (RBT 89,7 FM) DALAM PENYEBARAN INFORMASI VIRUS COVID-19 - Andy Armia; Rita Herlina (KAREBA : Jurnal Ilmu Komunikasi, 2020)
This research aims to determine the utilization of Radio Belitung Timur (RBT 89.7 FM) in spreading Covid-19 virus alert information to people in East Belitung area. This research methodology uses qualitative methodology with descriptive approach. Data collection techniques used are primary data through direct interviews with the two informants, namely the chief manager of RBT radio and one of rbt radio broadcasters and conduct observations, while secondary data is obtained from websites, documents, books and articles. The results of this study showed that the utilization of RBT radio in the delivery of Covid-19 virus alert information is very petrifying in responding to be ready to face this virus and its strategy in addition to broadcasting on the usual radio in general RBT utilizes social media facebook with live streaming on its account that is packed with Talkshow format and also by frequently playing Public Service Ads (ILM) Pandemic Covid-19. As a listener, beltim people are more accepting of the bribes of information provided and only a handful of people who want to ask via direct phone and also SMS/WA because most of the people are a bit reluctant and embarrassed to ask questions and afraid of the wrong things to ask about the Covid-19 virus problem in Beltim.  But with the ability of the broadcaster (radio host) in provoking the issue of questions, so that what the listener wants to ask is already represented by the radio broadcaster.